Patogenicidad de diferentes hongos entomopatógenos para el control de Aleurotrachelus socialis (Homoptera: Aleyrodidade) bajo condiciones de invernadero - Alean Carreño, I.; Morales Rodriguez, A.; Holguin, CM; Bellotti, Anthony C. (2004)
A complex of eight whitefly species associated with cassava exists in Colombia. The predominant species Aleurotrachelus socialis Bondar, which constitutes 92% of the total population and causes yield losses of up to 79% in field experiments. In order to offer cassava growers an alternative to chemical control to reduce costs and environmental degradation we assessed the pathogenicity of various strains of the entomopathogenic fungí Beauveria bassiana (Bálsamo) Vulllemin, Verticillium lecanii (Zímm.) Viegas and Paecilomyces fíonosoroseus (Wize) Brown fie Smith on different nymphal stages and eggs of A. socialis in order to determine the most susceptible developmental stage, select the most promising isolate and identify the lethal concentration (CL50). We also evaluated different commercial formulations of entomopathogenic fungí on the most susceptible developmental stage of A. socialis. We observed differences in mortality between the fungal species used and the control treatment. The V.lecanii strain CIAT 215 was selected as the most promising because it presented the highest mortality to A. socialis developmental stages (67,3%). The most susceptible stage were eggs cióse to hatching. We tested the strain CIAT 215 in seven concentrations on this stage and determinated that the CL50 was 1,4x107 conidia/ml with a confidence interval of 3,6x105-1,5x109 conidia/ml. The evaluated commercial formulations caused mortality of less than 50%, however, they were still statistically different than the control treatment.